Acid phosphatase activity in Malpighian tubules of Triatoma infestans Klug - Oliveira, Maria Tercília Vilela de Azeredo [UNESP]; Mello, MLS (Faculty Press, 1997)
Acid phosphatase activity was detected in the Malpighian tubules of the bloodsucking hemipteran, Triatoma infestans. The enzyme activity was especially prominent in the cytoplasmic globules which were assumed to be laminated 'concretions', which occur in the distal cells of the organ. It was also verified in the nuclei and in some cytoplasmic granules (lysosomes) of the proximal cells. The data indicated that lysosomes were involved with the nature or origin of the laminated concretions, but it is still questionable whether acid phosphatase activity exists in the nuclei.
Keywords: Triatoma infestans; Acid phosphatase; Malpighian tubules